Pengaruh Aplikasi Kompos TKKS Pada Media dan Auksin Terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq) di Pre Nursery - Rahmaniah Rahmaniah; Roswita Oesman (Universitas Teuku Umar, 2023)
Oil palm (Elaeis Guineensis Jacq) is a leading and main plantation commodity in Indonesia. Its main product consists of palm oil (CPO) which has high economic value. Applying compost is an effort to increase the production of oil palm plants. To support the growth of oil palm seedlings, growth regulators (ZPT) can also be given to plants in addition to fertilizing, because ZPT is an organic compound that functions to stimulate plant growth. This study aims to determine the effect of OPEFB compost application on media and auxin on the growth of oil palm seedlings (Elaeis Guineensis Jacq) in the Pre Nursery. This study used the Randomized Block Design (RBD) method. The factorial consists of 2 factors, namely: Factor I is the dose of OPEFB compost which is denoted (T) which consists of 4 levels, namely Without OPEFB compost (control) (T0), 40 gr/polybag (T1), 50 gr/polybag (T2), and 60 gr/ poly bag (T3). Factor II Auxin concentration symbolized (N) which consists of 4 levels, namely: Without Auxin (control) (A0), 1 cc Auxin /l Water (A1), 2 cc Auxin /l Water (A2), and 3 cc Auxin /l Water (A3). The results of this study indicated that the OPEFB compost treatment had a significant effect on seedling height, leaf length and leaf width. The higher the dose of OPEFB compost given up to 60 g/polybag, the higher the growth of oil palm seedlings. The auxin treatment significantly affected seedling height, leaf length, and leaf width. The higher the concentration of auxin given up to 3 cc/l of water, the higher the growth of the oil palm seeds.Keywords: Auxin, Oil Palm Seeds; EFB Compost